THE MODEL OF STUDENTS ENGLISH CLUB CONTRIBUTION TO WRITING MOTIVATION AND PUNCTUATION AWARENESS IMPROVEMENT - Nur Rahmiani; Norhayaty M. Malena (Journal of English Educational Study (JEES), 2020)
This work aims to analyze the existence of the English Club Project (ECP) for Vocational Midwifery Students (VMS) by developing an essay in terms of the output program relating to their professionalism. The program facilitates 30 students to build up motivation and awareness of punctuation in additional learning of writing skills. As it is developed from qualitative research, this article is based on the data collected through gathering diversified sources of evidence, organizing a chain of evidence, and having key-informants reviewing draft case study reports. The results present an additional learning model constructed by the representation of the ECP program. ECP is an informally productive community by providing activities and opportunities in increasing the motivation for writing and punctuation awareness. Students begin to understand that doing the writing is uncomplicated anymore after joining the extracurricular programs managed with structured and directed activities. Also, the facilitator provides valuable supports and integrates teaching methods with information and technology devices that made the learning activities quickly done—as for recommendations, strengthening the support to this model is necessary for the sustainability of this additional learning program.